Ennore, Promises Undelivered: How the Idea of Infinite Growth is Unmaking India. (May 2017) - Singh, TejInder; Kumar, Pooja; Kuttuva, Pradeep
The rapid industrialisation and urbanisation in India over the past few decades has resulted in severe environmental destruction and loss of traditional livelihoods, as well as worsened economic and social inequalities. Ennore, a northern suburb of Chennai is a classic example of this phenomenon. This photo essay presents the deleterious impacts of urbanisation on the artisanal fisherfolk of Ennore. The inherently unsustainable nature of water extraction for industries in this region coupled with lax regulations first destroyed the Ennore creek and consequently fisherfolk livelihoods. Dwindling fish catches have created an artificial demand for jobs, thereby resulting in formerly independent communities being completely enslaved to the development paradigm. The state's response has not been to fix environmental and community health problems in Ennore, but only to push for more growth and development. The essay argues that this toxic idea of growth needs to be dismantled first, if the degradation of livelihood commons is to be stopped.